Polychaetous annelids of the Ryukyu Islands - Okuda, Shiro (Bulletin of the Biogeographical Society of Japan, 1940)
None. Begins "Although many references to the Pacific Polychaetes are scattered throughout a number of papers dealing with the annelids, the polychaete fauna of the Ryukyu (Okinawa) Islands is scarcely known. So far as I could ascertain, only one Amphinomid, Notopygos mitskurii, has ever been reported by Izuka (1912) from Okinawa-zima. The present account is based upon the collection made in January, 1939 during my short stay at Okinawa-zima,, central group of the Ryukyu. Islands. The great majority were· collected by myself in littoral waters of Okinawa-zima, but a few of the specimens collected at Isigaki-zima of the southern Ryukyu Group were provided for me by the courtesy of Mr. S. Mikaye. Of 34 species herein recorded 14 have not been reported in the Japanese fauna, and a single one seems to represent a new species. The most interesting is the new addition to the rare and curious Capitellid genus Scyphoproctus established by Gravier in 1906"
World Polychaeta Database (WPolyDb)